On optimizing travel routes in Kathmandu Valley, Nepal using genetic algorithms - Pandey, Astha; Pokharel, Sujan; Karki, Ujjwal; Pant, Anand; Bhattarai, Saishab; Jha, Kanhaiya (Kathmandu University Journal of Science Engineering and Technology, 2025)
Effective route scheduling is crucial for reducing both travel time and expenses, particularly in industries like transportation and travel. One of the optimization methods known as the Travelling Salesman Problem (TSP), offers a useful structure for solving these issues, but because of its NP-complete characteristics result in the need for significant computational resources to solve it perfectly.In this study, we provide a unique approach to route optimization that makes use of a genetic algorithm (GA) and provides a heuristic approach which delivers almost optimal solutions in reasonable time. The concept applied in our methodology minimizes the distance between various destinations within Kathmandu Valley.